Cetuximab, fluorouracil and cisplatin with or without docetaxel for patients with recurrent and/or metastatic squamous cell carcinoma of the head and neck (CeFCiD): an open-label phase II randomised trial (AIO/IAG-KHT trial 1108) - Klinghammer, K.; Gauler, T.; Dietz, A.; Grünwald, V.; Stöhlmacher, J.; Knipping, S.; Schroeder, M.; Guntinas-Lichius, O.; Frickhofen, N.; Lindeman, H. W.; Fietkau, Rainer; Haxel, B.; et al. (European Journal of Cancer, 2019)
Background: The combination of cisplatin, 5-fluorouracil (5-FU) and cetuximab (PFC) is the reference first-line treatment for recurrent/metastatic (R/M) squamous cell carcinoma of the head and neck (SCCHN). We analysed whether treatment intensification by the addition of docetaxel to PFC improved efficacy in R/M SCCHN. Methods: A total of 180 patients with R/M SCCHN (1:1) were assigned to receive either cisplatin (40 mg/m2), docetaxel (40 mg/m2) and 5-FU (2000 mg/m2) at days 1 and 8 and cetuximab (400/250 mg/m2) at days 1, 8 and 15 (DPFC) or standard cisplatin (100 mg/m2) at day 1, 5-FU (1000 mg/m2) at days 1–4 and cetuximab (400/250 mg/m2) at days 1, 8 and 15 (PFC). Chemotherapy was repeated every 21 days and continued for a maximum of 6 cycles in absence of disease progression or limiting toxicity, followed by cetuximab maintenance (500 mg/m2 every 2 weeks). The primary end-point was progression-free survival (PFS). Results: A preplanned interim analysis for toxicity after 20 patients/arm revealed excessive grade 3 and 4 gastrointestinal (65%) and infectious toxicities (35%) in arm A, which led to dose reduction of cisplatin to 30 mg/m2 and 5-FU to 1000 mg/m2 for subsequent patients. With a median follow-up of 2 years, grade 4 toxicities were 21.3% vs. 30.8% for DPFC and PFC, respectively. More treatment-related deaths occurred with DPFC vs. PFC, with 11.2% and 6.6%, respectively. For DPFC and PFC, the median PFS was 6.3 vs. 6.4 months (hazard ratio [HR] = 0.97, p = 0.87), the median overall survival was 8.9 vs. 10.6 months (HR = 1.29 p = 0.1) and response rates were 38.2% vs. 31.9% (p = 0.9), respectively. Conclusions: DPFC failed to improve efficacy in R/M SCCHN. On the contrary, a high toxicity and mortality rate was detected in both arms, which underscores the vulnerability of patients with R/M SCCHN, and research on the need for further optimisation of the front-line chemotherapy backbone is ongoing.
CRIS-Team Scopus Importer:2019-10-18
Keywords: Cetuximab; Chemotherapy; Docetaxel; Head and neck cancer; Randomised trial